PSYCHOLOGICAL NUANCE IN Q.S. YUSUF: A Study on Thematic Tafseer with Psychological Approach - Mustaqim, Abdul; Khalid, Muhammad (ULUL ALBAB Jurnal Studi Islam, 2021)
Surah Yusuf is the only Surah in The Quran telling the story of Prophet Yusuf. It contains several important psychological dimensions to teach people about moral. However, the study of psychological dimensions is rarely (or never) conducted. Using thematic method and psychological approach, this article aims to describe and analyze comprehensively the dimensions of psychological emotions of Prophet Yusuf’s story. As a result, this research concludes that there are psychological emotional terms in the story, such as fear (khawf), sadness (ḥuzn), jealousy (ghirah), envy (ḥasad), hate (kurh), joy (faraḥ), lust (shahwah), and regret (nadm). Actually, these emotions are good for self-protection, competition, and self-defense. From the story, humans can learn how to control these emotions well, so they do not fall into difficulty. The reason why the Quran pays attention to psychological emotions in the story of Yusuf is to teach that all humans including the prophets have psychological emotions. So, they should be wise in dealing with emotions and to adjust or control them.